Madduma bandara” and the last king of sri lanka “sri wickrama rajasimha”: changing perspectives of representation of the “child hero” and “despotic king” in genres of theatre in colonial times - De zoysa, A. (University of Jaffna, 2012)
On the orders of Sri Wickrama Rajasinha, the last king of Kandy Madduma Bandara, the nine year old Son of Ähalepola, the first Adigar or Prime Minister to the King of Kandy, was beheaded on 17th March 1814 along with his siblings. Ten months later, the Kandyan Kingdom came under the British rule. It is reported that the boy most bravely encountered his executor, making him a role model for Sinhala children and the youngest national hero. Narrations of the cruel punishment and the loss of sovereignty of the island became one of the most popular topics on the Sri Lankan stage. In 1870 Don Philippu Sinhgo published his “Ahalepola Nadagama” which was performed in the same year in Colombo. Based in independent historical sources, John de Silva performed his drama “Sri Wickrama Rajasinha” in 1906 at the tower Hall. Inspired by the most popular play of John de Silva Charles Dias reworked the plot for a further play a few years later. The objective of this research is to show how the historical characters were re fashioned to meet the needs of the play write and the audience living under colonial rule. The research will first view the characterization of the main figures: Sri Wickrama Rajasingha, the “Vadiga” King of South Indian origin, Ahalepola Kumarihami as the virtuous Kandyan women, embodying the chaste qualities of the Sinhala Women, Madduma Bandara, the child hero, Pilimatalawa Adigar, who betrays the King, and the other Radala Men in the Kandyan court. The adjectives used to describe the characters change over the three decades. The research will then work out the motivation for the author to portray the characters in the particular way. For this the closing passages of each play is worth comparing asking the question, who is to be blamed for the loss of sovereignty of the island.